INVESTIGATION OF THE METHOD OF PROCESSING HOLES WITH A ROTARY CUP CUTTER WITH SURFACING - Donenbayev, Bakytzhan; Sherov, Karibek; Mazdubay, Assylkhan; Sherov, Aybek; Mussayev, Medgat; Gabdyssalyk, Riza; Ainabekova, Saule; Taskarina, Aizhan; Tussupova, Sayagul (Journal of Applied Engineering Science, 2021)
This article presents the experimental study results of the process of rotational friction holes boring using a cup cutter surfaced by STOODY M7-G material. As a result of experimental studies, the following quality indicators were achieved: surface roughness within Ra=10÷1,25 micrometer; surface hardness within HB 212-248. Using a cup cutter surfaced by STOODY M7-G material in case of rotational friction boring of large-diameter holes for large-sized parts can improve processing performance in comparison with cutting tools equipped with hard metal plates and provided the required surface roughness. Preliminary calculations showed that the manufacture of cup cutters from non-instrumental materials reduces the cost of the cutting tool by 5-7 times and the cost of the operation by 1.5-2 times.